A lack of role for antibodies in regulating Helicobacter pylori colonization and associated gastritis. Issue 2 (23rd February 2020) - Arshad, Umar; Sarkar, Sohinee; Alipour Talesh, Ghazal; Sutton, Philip
Abstract: Background: Helicobacter pylori occupy a unique niche, located within the mucus layer lining the stomach, and attached to the apical surface of the gastric epithelium. As such, antibodies would be expected to play a major role in regulating infection and/or pathogenesis. However, experiments using antibody‐deficient mice to study gastric helicobacter infection have yielded inconsistent results, although some pointed toward antibodies increasing colonization levels and decreasing gastritis severity. The variability in these studies is possibly due to their use of nonmatched wild‐type controls. This current study presents the first evaluation of the role of antibodies in H pylori infection by comparing antibody‐deficient mice with matched wild‐type siblings. Methods: Matched wild‐type and antibody‐deficient μMT mice were generated by heterozygous crossings. In two separate experiments, appropriately genotyped sibling littermates were infected with H pylori for 4 months and then sera and stomachs were collected. Results: There was no difference in H pylori colonization levels between infected μMT mice and sibling wild‐type controls. Similarly, there was no significant difference in the severity of gastritis between these groups of mice, although there was a trend toward less severe gastritis in μMT mice which was supported by a significantly lower IFNγ (Th1) gastric cytokine response. Conclusions: Comparing matched antibody‐deficient and antibody‐competent mice indicates that an antibody response does not influence H pylori colonization levels. Contrary to previous studies, these results suggest antibodies might have a minor pro‐inflammatory effect by promoting gastric Th1 cytokines, although this did not translate to a significant effect on gastritis severity.